Modulation of NF-?B and Nrf2 pathways by lycopene supplementation in heatstressed poultry - Şahin, Kazım (Taylor & Francis Ltd, 2015)
Heat stress is characterised by reduced antioxidant status, and is one of the physiological alterations in response to exposure to higher temperatures in birds, which results in increased oxidative stress and immune suppression. The transcription entity nuclear factor-kappa light chain enhancer of B cells (NF-kappa B) controls the expression of genes involved in a number of physiological responses, including immune inflammatory responses, acute-phase inflammatory responses, oxidative stress responses, cell adhesion, differentiation, and apoptosis. The nuclear factor-2 erythroid related factor-2 (Nrf2), the redox-sensitive transcription factor, plays a key role in regulating induction of phase II detoxifying or antioxidant enzymes. Thus, activation of Nrf2 is considered to be an important molecular target of many anti-stressor agents. However, during heat stress conditions this regulation is disturbed offering an opportunity for therapeutic intervention. Heat stress is a condition in which the expression pattern of NF-kappa B and Nrf2 changes. To reduce the negative effects of heat, antioxidants are used in poultry diets for their anti-stress effects, associated with improved nutrient utilisation. For instance, lycopene, a powerful antioxidant, is particularly important because of its ability to quench reactive oxygen. This review focuses on the role of the NF-kappa B and Nrf2 in heat stress condition and summarises the therapeutic outcomes of lycopene in feed, targeted at the NF-kappa B and Nrf2 pathways in heat-stressed poultry.
Keywords: heat stress; lycopene; NF-kappa B; Nrf2; poultry